2014
DOI: 10.1097/prs.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Single-Stage Augmentation-Mastopexy

Abstract: This meta-analysis encompassed 4856 cases of simultaneous augmentation-mastopexy. Study heterogeneity was high because of differences in surgical techniques, outcome definitions, and follow-up durations. This review suggests that with careful patient selection, pooled complication and reoperation rates for single-stage augmentation-mastopexy are acceptably low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 35 publications
1
68
1
7
Order By: Relevance
“…For example, the hematoma rate following breast augmentation in the current literature ranges from 0.6% to 5.7%, but it was found to be 1% in our study. [16][17][18][19] Likewise, the incidence of hematoma after facelift surgery ranges from 0.2% to 12.9% in the literature, but our analysis showed an incidence of 1%. [6][7][8][9][10][11][12][13][14][15] Although prior studies on body contouring procedures showed hematoma rates ranging from 3% to 15%, our study showed lower rates after abdominoplasty at 1.1%, thigh lifts at 2%, and lower body lifts at 4%.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For example, the hematoma rate following breast augmentation in the current literature ranges from 0.6% to 5.7%, but it was found to be 1% in our study. [16][17][18][19] Likewise, the incidence of hematoma after facelift surgery ranges from 0.2% to 12.9% in the literature, but our analysis showed an incidence of 1%. [6][7][8][9][10][11][12][13][14][15] Although prior studies on body contouring procedures showed hematoma rates ranging from 3% to 15%, our study showed lower rates after abdominoplasty at 1.1%, thigh lifts at 2%, and lower body lifts at 4%.…”
Section: Discussionmentioning
confidence: 54%
“…Reported rates for hematomas vary depending on the procedure performed and the patient population, ranging from 3% to 15% in body contouring surgery, [3][4][5] 0.2% to 12.9% in facelift and facial rejuvenation procedures, [6][7][8][9][10][11][12][13][14][15] and 0.6% to 5.7% in breast augmentation surgery. [16][17][18][19] Several risk factors predisposing towards postoperative bleeding and hematoma formation have been previously identified, including demographic factors such as gender and smoking status, medical co-morbidities such as hypertension and malignancy, anticoagulant medications, operative and anesthetic techniques, as well as postoperative management. 4,16,20,21 Most studies in the current literature examining the incidence and risk factors for hematoma formation are limited by retrospective design, small sample size, and single institution analyses of isolated aesthetic surgical procedures.…”
mentioning
confidence: 99%
“…Numerous skin patterns and pedicles are used. 28,29 Algorithms can be complicated. 3032 Lee et al 8 published an algorithm based on skin measurements and recommended staging for patients with more than 6 cm of vertical skin excess.…”
Section: Discussionmentioning
confidence: 99%
“…68,10,1216,20 However, prepectoral placement is a valid alternative, particularly in women with adequate breast tissue, and avoids an animation deformity. There is a general preference for silicone gel implants 29 although some surgeons more commonly insert saline implants. 6,20 Silicone gel implants have traditionally been favored for a more natural feel characteristic and possibly less rippling.…”
Section: Discussionmentioning
confidence: 99%
“…18e31 As stated in a recent meta-analysis of one stage mastopexy implant it has been difficult to make evidence-based decisions weighing the potential added risks of complications and poor aesthetic outcomes against the benefits of a single-stage procedure. 29 For the patient with grade 3 ptosis the risks are highest and it is in this group in whom a breast augmentation only or mastopexy alone would likely give a suboptimal outcome.…”
Section: Introductionmentioning
confidence: 98%